Yield components in sesame Sesamum indicum L. (Pedaliaceae) cultivars, in the department of Sucre, Colombia (2018)
Sesame Sesamum indicum L. (Pedaliaceae) seeds have a great potential for the agricultural sector in the department of Sucre (Colombia), mainly in the elaboration of food products and biofuels, due to its favorable oil and nutrient content. The aim of this study was to establish yield components in sesame through the description of components such as: fertile nodes in stem, capsules per fertile node, seeds per capsule, weight of 1,000 seeds, number of branches and fertile nodes per branch, as well as yield and oil content in seed, for the cultivars Criollo, ICA Matoso and Chino Rojo, in the last quarter of 2015. The variables were analyzed through a randomized complete block design and simple regression models between yield per plant and components. A significant effect of the variety factor was found on the components, except for number of fertile nodes in the branch and greater number of fertile nodes in the stem (30), seeds per capsule (68) and average weight of one thousand seeds (2.86 g) in the Criollo and ICA Matoso cultivars. Likewise, average seed yields of 1,289.8 kg/ha in the Criollo cultivar were found, as well as oil content of ca. 49% in the cultivar ICA Matoso. Similarly, the yield component with the highest linear association was average seed weight, which allows the selection of the best performing cultivars among the ones studied.